Perlindungan Hukum Pelaku Usaha terhadap Ulasan Digital Menyesatkan: Rekonstruksi Tanggung Jawab Platform di Indonesia - Andriana Andriana; Liza Marina; Ani Purwati (SENTRI: Jurnal Riset Ilmiah, 2026)
The rapid development of the digital platform economy has transformed consumer decision-making patterns through online reviews as a primary source of information. However, the increasing prevalence of misleading digital reviews, including fake reviews facilitated by automation technologies and generative artificial intelligence, raises significant legal concerns, particularly regarding the protection of business actors. This study aims to analyze the legal framework governing the protection of business actors against misleading digital reviews and to evaluate the legal responsibility of digital platforms within Indonesia’s digital economic ecosystem. This research employs a normative legal method using statutory and conceptual approaches through the analysis of regulations related to electronic transactions, consumer protection, and platform liability, complemented by comparative international practices. The findings indicate that the existing national regulatory framework has not comprehensively regulated platform responsibility in moderating digital reviews and has not provided effective legal remedies for business actors. This condition creates an imbalance in legal relations among users, business actors, and platform providers. The study concludes that regulatory reconstruction is necessary through strengthening content moderation obligations, review verification mechanisms, and proportional platform liability to establish a fair and equitable digital economic ecosystem.